Evaluation of the pharmacokinetics of trazpiroben (TAK‐906) in the presence and absence of the proton pump inhibitor esomeprazole - Jatinder Kaur Mukker; George Dukes; Lisi Wang; Susanna Huh; Polyna Khudyakov; Mitsuhiro Nishihara; Chunlin Chen (Wiley, 2022)
Abstract Trazpiroben, a dopamine D2/D3 receptor antagonist under development to treat gastroparesis, displays decreasing solubility with increasing pH. This single‐sequence, open‐label, two‐period, crossover study evaluated the effect of esomeprazole, a proton pump inhibitor that raises gastric pH, on the single‐dose pharmacokinetics, safety, and tolerability of trazpiroben in healthy adults (NCT03849690). In total, 12 participants were enrolled and entered period 1 (days 1-3), receiving a single oral dose of trazpiroben 25 mg on day 1. After a 4‐day washout, participants then entered period 2 (days 8-13) and received esomeprazole 40 mg once daily on days 8-12, with a single oral dose of trazpiroben 25 mg co‐administered 1 h post esomeprazole dosing on day 11. Geometric mean area under the curve from time 0 extrapolated to infinity (AUC∞) and maximum plasma concentration (Cmax) values were generally similar when trazpiroben was administered alone versus alongside esomeprazole (AUC∞, 44.03 vs. 38.85 ng h/ml; Cmax, 19.76 vs. 17.24 ng/ml). Additionally, the associated geometric mean ratio (GMR; co‐administration: administration alone) 90% confidence intervals (CIs) suggested no clinically meaningful difference between treatment groups (AUC∞, GMR 0.88, 90% CI 0.78-1.00; Cmax, 0.87, 90% CI 0.70-1.09). Mean apparent first‐order terminal elimination half‐life values were similar between treatments, illustrating co‐administration with esomeprazole had minimal effect on trazpiroben elimination. Trazpiroben was well‐tolerated in healthy adults following administration alone and alongside esomeprazole, with no clinically relevant adverse events reported. The lack of evidence of any clinically meaningful drug-drug interaction supports the co‐administration of esomeprazole with trazpiroben.